Association of type II secretory phospholipase A2 and surfactant protein D with the pulmonary oxygenation potential in patients with septic shock during polymyxin‐B immobilized fiber‐direct hemoperfusion. Issue 5 (13th September 2016) - Ishibe, Yoriko; Shibata, Shigehiro; Takahashi, Gaku; Suzuki, Yasushi; Inoue, Yoshihiro; Endo, Shigeatsu
Abstract: This study was undertaken to analyze the association of type II secretory phospholipase A2 (sPLA2 ‐II) and surfactant protein D (SP‐D) with the pulmonary oxygenation potential in patients with septic shock during polymyxin‐B immobilized fiber‐direct hemoperfusion (PMX‐DHP). The study was conducted in 25 patients with acute lung injury (ALI) or acute respiratory distress syndrome (ARDS). PMX‐DHP lowered the blood endotoxin level in all patients. Following PMX‐DHP, there were decreases from day 0 → day 1 → day 2 in both the mean plasma sPLA2 ‐II level (340 → 260 → 189 ng/mL) and plasma SP‐D level (483 → 363 → 252 ng/mL). The PaO2/FiO2 ratio ( P/F ratio) rose (210 → 237 → 262) in all patients. Upon the onset of ALI or ARDS, there was a significant negative correlation between the sPLA2 ‐II level and the P/F ratio. Furthermore, there was a significant positive correlation between the sPLA2 ‐II and TNF‐α levels. The results suggest that as the blood endotoxin levels were lowered by the PMX‐DHP, the inflammatory reactions were suppressed, with suppressed formation of sPLA2 ‐II and improved pulmonary oxygenation potential. The results also suggested possible involvement of TNF‐α in the production of sPLA2 ‐II.